2017
DOI: 10.17159/2413-3051/2016/v26i4a2089
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fire-ignition methods and stove ventilation rates on gaseous and particle emissions from residential coal braziers

Abstract: Despite extensive electrification of low-income residential areas on the South African

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The method was often demonstrated in poorly ventilated braziers resulting in elevated smoke emissions, in some cases worse compared to the traditional fire ignition method. The research team at the SeTAR Centre, University of Johannesburg has demonstrated that Basa njengo Magogo fire ignition method coupled with an optimised wellventilated brazier, results in improved combustion efficiency and reduced particle (visible smoke) emissions [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…The method was often demonstrated in poorly ventilated braziers resulting in elevated smoke emissions, in some cases worse compared to the traditional fire ignition method. The research team at the SeTAR Centre, University of Johannesburg has demonstrated that Basa njengo Magogo fire ignition method coupled with an optimised wellventilated brazier, results in improved combustion efficiency and reduced particle (visible smoke) emissions [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…The devices were categorised into high, medium and low ventilation rates, depending on the total air hole area. Quantitative results of ventilation rates and other imbaulas used in this study are presented elsewhere (see Makonese et al, 2015).…”
Section: Experimental Stoves and Fuel Analysismentioning
confidence: 99%
“…The coal was crushed and sieved to maintain a mean particle size diameter of 40-60 mm. Uniform coal size distribution was used for each fuel category to minimise errors inherent in the use of different coal sizes (Makonese et al, 2015). Each batch of fuel was analysed for moisture content before testing.…”
Section: Experimental Stoves and Fuel Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the traditional BLUD method involves placing the kindling and igniting it at the bottom of the brazier or stove, with the bulk of the fuel placed on top of the burning kindling. [23][24][25] The TLUD method is estimated to result in a 70-90% reduction in ambient particulate emissions and a 20% reduction in coal consumption at no additional cost to households. 26,27 For several years (from 2009 to 2014), the implementation of the BnM rollout became a national priority energy intervention programme.…”
Section: Introductionmentioning
confidence: 99%